2017
DOI: 10.3847/1538-4357/aa78fc
|View full text |Cite
|
Sign up to set email alerts
|

An ALMA Survey of CO Isotopologue Emission from Protoplanetary Disks in Chamaeleon I

Abstract: The mass of a protoplanetary disk limits the formation and future growth of any planet. Masses of protoplanetary disks are usually calculated from measurements of the dust continuum emission by assuming an interstellar gas-todust ratio. To investigate the utility of CO as an alternate probe of disk mass, we use ALMA to survey 13 CO and C 18 O J=3-2 line emission from a sample of 93 protoplanetary disks around stars and brown dwarfs with masses from M 0.03 to 2  in the nearby Chamaeleon I star-forming region… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(151 citation statements)
references
References 116 publications
8
142
1
Order By: Relevance
“…However, very recent work by Long et al (2017) estimate the gas mass around ESO-Hα 569 from ALMA 13 CO line emission and find only~M 1.3 Jup of gas mass in the disk, although optical depth effects and details of the CO freeze-out are likely to introduce major sources of uncertainty. Combined with our own dust mass estimate, this gives an uncharacteristically low gas-to-dust ratio of only ∼2.…”
Section: Surface Density Exponentmentioning
confidence: 99%
“…However, very recent work by Long et al (2017) estimate the gas mass around ESO-Hα 569 from ALMA 13 CO line emission and find only~M 1.3 Jup of gas mass in the disk, although optical depth effects and details of the CO freeze-out are likely to introduce major sources of uncertainty. Combined with our own dust mass estimate, this gives an uncharacteristically low gas-to-dust ratio of only ∼2.…”
Section: Surface Density Exponentmentioning
confidence: 99%
“…In this case, CO or gas depletion may be even more severe than currently estimated, although large line optical depths may also contribute to underestimates of the amounts of CO or gas (e.g. Ansdell et al 2016;Barenfeld et al 2016;Long et al 2017). Highresolution, multi-band ALMA surveys of protoplanetary disks can determine whether other disks have continuum emission and spectral index profiles similar to that of TW Hya.…”
Section: Comparison To Other Sourcesmentioning
confidence: 99%
“…Barenfeld et al 2016;Long et al 2017;Miotello et al 2017). As the nearest disk, TW Hya may be the most important test case for breaking the degeneracy.…”
Section: Comparison To Other Sourcesmentioning
confidence: 99%
“…Previous studies of 1-3 Myr old disks have found evidence for a low CO abundance relative to dust throughout the disk (Dutrey et al 2003;Chapillon et al 2008;Williams & Best 2014;Hardy et al 2015;Long et al 2017). Ansdell et al (2016) used observations of optically thin 13 CO and C 18 O emission to measure the gas-to-dust ratios of 62 disks in 1-3 Myr old Lupus complex, finding that the majority of sources had a gas-to-dust ratio below the ISM value of 100 assuming an ISM abundance of CO relative to H 2 (see also Miotello et al 2017).…”
Section: Comparing Dust and Comentioning
confidence: 99%